The current clinical trial landscape in idiopathic inflammatory myopathies - Nikola Wilk; Julie Paik; Merrilee Needham; Hector Chinoy (Current Opinion in Rheumatology, 2026)
Purpose of review In recent years, advances in the understanding of idiopathic inflammatory myopathies (IIM) pathogenesis have led to the development of targeted therapies directed against key immune pathways. This review highlights recent advances in clinical trials, emerging therapeutic strategies, and the rapidly evolving treatment landscape in IIM, reflecting the continued expansion of the therapeutic armamentarium. Recent findings Multiple clinical trials have evaluated therapeutics directed against key immune pathways implicated in IIM, including B-cell depletion, T-cell co-stimulation, type I interferon (IFN) signaling, fragment crystallizable receptor (FcRn) inhibition and Janus kinase (JAK) /STAT blockade. Promising results have been reported with agents such as JAK inhibitors, FcRn antagonists, anti-IFN therapies, and chimeric antigen receptor (CAR) T-cell approaches in selected patients. Several additional experimental trials are ongoing to evaluate novel therapeutic agents. Summary Several recent landmarks clinical trials in IIM suggest that targeted therapies directed at key immune pathways may improve disease control beyond conventional immunosuppression, supporting a shift toward mechanism-based treatment approaches in clinical practice. The rapid and expanding growth of clinical studies in IIM reflects an unprecedented acceleration in therapeutic development, underscoring the progress in the field.